PEMBELAJARAN YANG BERORIENTASI HIGHER ORDER THINGKING SKILLS: MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DENGAN PEMBELAJARAN YANG BERORIENTASI HIGHER ORDER THINGKING SKILLS - dra. Hartini dra. Hartini (Eksponen, 2021)
Indonesian language lessons are related to how to study science through concepts systematically, and facts obtained through discovery. However, in practice, the learning model applied to students through conventional techniques is the dominant technique, while other learning models such as discussion, experimentation, inquiry, and cooperative learning are rarely carried out. In the conventional learning process, students are less creative to develop thinking skills, so they become passive and less involved in learning. Schools as an educational institution have an important role in efforts to develop and realize the potential of students. The development of this potential can be started by growing students' thinking skills and abilities. In this case, think critically, creatively, logically, systematically, and argumentatively. These abilities need to be possessed by students, as a provision in dealing with the problems that will be faced, both problems that exist in school and problems that exist in everyday life. To achieve this, the author tries to change the learning method oriented to higher order thinking skills by using the Discovery Based Learning model.